Analisis Pengendalian Internal Piutang BPJS Kesehatan Untuk Meningkatkan Efektivitas Pengelolaan Piutang di RSUD Kota Mataram - Rahimana, Putri Yunita; Fitriyah, Nur; Mariadi, Yusli (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine how internal control at the RSUD Kota Mataram, especially on BPJS Kesehatan receivables. The research method used is descriptive qualitative with primary data sources to obtain information related to the application of internal control based on the five components of COSO internal control, in addition to knowing the turnover of receivables and the average days of collection of BPJS Kesehatan receivables, then the data collection technique is carried out by means of interviews, observation, and documentation, then data analysis is carried out in the form of reduction, data display, and conclusion drawing. The results of this study indicate that the internal control of BPJS Kesehatan receivables at the RSUD Kota Mataram is effective, indicated by the existence of a control environment, risk assessment, control activities, information and communication, and supervision that already exists or is carried out on BPJS Kesehatan receivables. Meanwhile, based on RTO and ACP, it shows that BPJS Kesehatan receivables in 2020 are more efficient than in 2021 and 2022, this is because the number of BPJS Kesehatan receivables for each year has increased so that the capital embedded is getting bigger so that the longer it takes to become cash.